Mutation de la grande entreprise en contexte italien : Ansaldo - Patrick Fridenson (L'Atelier du CRH)
Alain Dewerpe’s posthumous book, which deals with the history of Ansaldo from 1853 to 1933, a firm based in Genoa which focused on steelmaking and mechanical engineering, innovates in many ways. It challenges the dominant view of the large corporation, as it shows the strength of specialty production, still present today. It challenges the prevailing definition of business history, as it centers on the importance of work (both by white collars as by blue collars), of science and of accountancy. Finally it explains why Fordism, which the company adopted during World War I, was abandoned in the bickering atmosphere of the 1920s.